Susceptibility to Phytophthora cinnamomi of the commonest morphotypes of Holm oak in southern Spain (Forest Pathology, 2012)
The four main morphotypes of Holm oak (Quercus ilex subsp. ballota) present in Andalusia (expansa, macrocarpa, microcarpa and rotundifolia) were infected with Phytophthora cinnamomi to determine their susceptibility to the root pathogen. No large differences were found among the four morphotypes in the infection of roots, which always showed a high degree of necrosis. However, the different responses of the foliage to infection separated the four morphotypes of Holm oak into three groups: very susceptible (microcarpa), susceptible (expansa) and moderately susceptible (rotundifolia and macrocarpa). The natural hybrid Q. ilex ballota–Q. faginea exhibited a low level of root and foliar symptoms when infected with P. cinnamomi. Quercus faginea could be considered as a source of resistance to P. cinnamomi in future breeding programmes.

The role of yellow lupin (Lupinus luteus) in the decline affecting oak agroforestry ecosystems (Forest Pathology, 2011)
Phytophthora cinnamomi is a soilborne pathogen causing root rot in Mediterranean Quercus species growing in dehesa rangeland ecosystems. Recently, it has been reported causing wilting and death of Lupinus luteus (yellow lupin), a spontaneous plant in southern Spain rangelands, but also frequently sowed for livestock grazing. In soils artiﬁcially infested with P. cinnamomi chlamydospores and planted with diﬀerent cultivars of yellow lupin, a signiﬁcant increase in the density of propagules was detected in comparison with the initial levels of inoculum and with the infested but not planted soil (control). In oak-rangelands in which yellow lupine was planted, isolation and counting of colonies of P. cinnamomi from soil samples have shown the ability of this plant to maintain or even increase the inoculum density and thus facilitate the infection of trees. Results suggested that cultivation of yellow lupin in oak-rangeland ecosystems should be avoided whether oak trees are aﬀected by root disease caused by P. cinnamomi or not. This leguminous plant can act as an inoculum reservoir or even enhance inoculum soil levels available for oak root infections, exacerbating the oak decline severity in the region.

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.

Pathogenicity of Pythium spiculum and P-sterilum on feeder roots of Quercus rotundifolia (PLANT PATHOLOGY, 2008)
APS

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.

Botryosphaeria and Related Taxa Causing Oak Canker in Southwestern Spain (Plant Disease, 2003)
ABSTRACT Although root disease caused by Phytophthora cinnamomi is considered to be the most frequent and damaging disease associated with Quercus spp. decline in southwestern Spain, cankers commonly are observed on branches of declining Mediterranean Quercus spp. in this region. In surveys carried out in eight declining Quercus forests, strips of necrotic inner bark were common on diseased branches. Botryosphaeria stevensii, B. dothidea, and Diplodia sarmentorum consistently were isolated from these branches. Isolates of all three species caused cankers when inoculated onto excised Quercus branches. Inoculations on healthy branches in the field also induced canker development, but only B. stevensii caused lesions that girdled and killed the branches. The optimum temperature for in vitro growth of B. stevensii and B. dothidea was above 25°C, with slow growth at 35°C. In contrast, D. sarmentorum had an optimum temperature for growth of about 21°C, and did not grow at 35°C. The common occurrence and wide distribution of these pathogens, their association with cankers, and their ability to infect Quercus spp. suggest that they may contribute to the Quercus spp. decline in southwestern Spain.
doi: 10.1094/PDIS.2003.87.12.1515

Analysis of dehesas with multiple use. Physical and economic indexes of sustainable management (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
The wide surface that dehesas hold in Spain, together with their economic, social and environmental importance, give enough justification to the researchs that widen the scientific knowlege about the economics of dehesa systems. However, the dehesa agroforestry farms do not appear in the different statistical documentary sources of the Agricultural Accounting Net. The lack of technical-economic data about these systems impede neither to observe the effects of the Common Agricultural Policy on the natural environment, nor to know as a whole the dynamics and structure of their flows and the stock of resources and income. This paper deals with the technical and economic management of dehesas in the field of the environmental economics. Its main aim has been to carry out an analytical case study. In order to develop it, four dehesa farms in the Southwest of the Badajoz Province were selected. These farms have collaborated on the development of the Research Project UE CAMAR CT 90-28 ``Technical and economic analysis of dehesa and montado systems{''}. Its importance lies in the basis of the case analysis, with a description of the systems and an identification of the structure and dynamics of their resources, either at physical and economic level.